Evolving Crisis Standards of Care and Ongoing Lessons from COVID-19: Proceedings of a Workshop Series - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Crisis Standards of Care (CSC) inform decisions on medical care during a large-scale crisis such as a pandemic or natural disaster, eliminating the need to make these decisions at the bedside without protections or guidance. Numerous points throughout the COVID-19 pandemic have demonstrated the necessity of this type of crisis planning. The National Academies of Sciences, Engineering, and Medicine Forum on Medical and Public Health Preparedness for Disasters and Emergencies convened a series of public workshops to examine the experiences of healthcare providers during the COVID-19 pandemic and identify lessons that can inform current and future CSC planning and implementation. The workshops examined staffing and workforce needs, planning and implementation of CSC plans, and legal, ethical, and equity considerations of CSC planning. Topics of discussion included improving coordination between the bedside and boardroom, increasing buy-in from elected officials, expanding provider engagement, and addressing health equity issues. This publication summarizes the presentation and discussion of the workshops.

Medical Surge Capacity: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
During natural disasters, disease pandemics, terrorist attacks, and other public health emergencies, the health system must be prepared to accommodate a surge in the number of individuals seeking medical help. For the health community, a primary concern is how to provide care to individuals during such high demand, when the health system's resources are exhausted and there are more patients than the system can accommodate. The IOM's Forum on Medical and Public Health Preparedness for Catastrophic Events held a workshop June 10-11, 2009, to assess the capability of and tools available to federal, state, and local governments to respond to a medical surge. In addition, participants discussed strategies for the public and private sectors to improve preparedness for such a surge. The workshop brought together leaders in the medical and public health preparedness fields, including policy makers from federal agencies and state and local public health departments; providers from the health care community; and health care and hospital administrators. This document summarizes the workshop.

Preparedness, Response, and Recovery Considerations for Children and Families: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Preparedness, Response and Recovery Considerations for Children and Families is the summary of a workshop convened in June, 2013 by the Institute of Medicine Forum on Medical and Public Health Preparedness for Catastrophic Events to discuss disaster preparedness, response, and resilience relative to the needs of children and families, including children with special health care needs. Traditional and non-traditional medical and public health stakeholders from across federal, state, and local government health care coalitions, community organizations, school districts, child care providers, hospitals, private health care providers, insurers, academia, and other partners in municipal planning met to review existing tools and frameworks that can be modified to include children's needs; identify child-serving partners and organizations that can be leveraged in planning to improve outcomes for children; highlight best practices in resilience and recovery strategies for children; and raise awareness of the need to integrate children's considerations throughout local and state emergency plans. Communities across the United States face the threat of emergencies and disasters almost every day, natural and man-made, urban and rural, large and small. Although children represent nearly 25 percent of the U.S. population, current state and local disaster preparedness plans often do not include specific considerations for children and families. The preparedness and resilience of communities related to children will require a systems framework for disaster preparedness across traditional and non-traditional medical and public health stakeholders, including community organizations, schools, and other partners in municipal planning. This report examines resilience strategies that lead to successful recovery in children after a disaster and discusses current approaches and interventions to improve recovery in children.